THE USE OF GUESSING GAME TO IMPROVE LEARNERS’ SPEAKING ABILITY - Dwiputra, Rhevaldi Arif; Sada, Clarry; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research is to improve students’ speaking ability, especially in fluency and accuracy. This research was conducted at the eight grade students of SMPN 3 Pontianak in academic year 2017/2018. In this research, the subject is class VIIIF that consists of 38 students. The researcher conducted a classroom action research. The data were collected by observation and measurement technique. The tools of data collecting were observation checklist, field note, and scoring rubric for assessing speaking (performance test). Guessing game was used as the technique in this research which was conducted in two cycles. The research findings showed that the mean score of students’ speaking test improved from 1.68 for accuracy and 1.84 for fluency in the first cycle to 2.13 for accuracy and 2.26 for fluency in the second cycle. The improvements of this study were particularly in students’ speaking aspect, especially accuracy and fluency. Keywords: Speaking, accuracy and fluency, guessing game.